Mathematical modelling of the most effective goal of cholesterol-lowering treatment in primary prevention - Handrean Soran; Safwaan Adam; Paul Durrington; Zohaib Iqbal (BMJ Open)
Objective To compare quantitatively different recommended goals for cholesterol-lowering treatment in the primary prevention of atherosclerotic cardiovascular disease (ASCVD).Design Outcomes at pretreatment low-density lipoprotein (LDL) cholesterol concentrations from 2 to 5 mmol/L and 10-year ASCVD risk from 5% to 30% were modelled, using the decrease in risk ratio per mmol/L reduction in LDL cholesterol derived from randomised controlled trials (RCTs) of cholesterol-lowering medication.Data source Summary statistics from 26 RCTs comparing treatment versus placebo or less versus more effective treatment and 12 RCTs in which statin was compared with a higher dose of the same statin or with a similar statin dose to which an adjunctive cholesterol-lowering drug was added.Setting The different recommended goals are: (1) LDL cholesterol≤2.6 mmol/L (100 mg/dL); (2) LDL cholesterol≤1.8 mmol/L (70 mg/dL); (3) non-high density lipoprotein (HDL) cholesterol decrease of ≥40%; or (4) LDL cholesterol≤1.8 mmol/L (70 mg/dL) or decreased by ≥50% whichever is lower.Participants RCT participants.Interventions Statins alone or in combination with ezetimibe or proprotein convertase subtilisin/kexin type 9 inhibitors.Main outcome measures For each of the recommended therapeutic goals, our primary outcome was the number of events prevented per 100 people treated for 10 years (N100) and the number of needed to treat (NNT) to prevent one event over 10 years.Results At pretreatment LDL cholesterol 4–5 mmol/L, all four goals provided similar benefit with N100 1.47–16.45 (NNT 6–68), depending on ASCVD risk and pretreatment LDL cholesterol. With initial LDL cholesterol in the range 2–3 mmol/L, the target of 2.6 mmol/L was the least effective with N100 between 0 and 2.84 (NNT 35–infinity). The goal of 1.8 mmol/L was little better. However, reductions in non-HDL cholesterol by ≥40% or of LDL cholesterol to 1.8 mmol/L and/or by 50%, whichever is lower, were more effective, delivering N100 of between 0.9 and 9.33 (NNT 11–111). Percentage decreases in LDL cholesterol or non-HDL cholesterol concentration are more effective targets than absolute change in concentration in people with initial values of <4 mmol/L.Conclusions The LDL cholesterol target of 1.8 mmol/L is most effective when initial LDL cholesterol is >4 mmol/L. The time has probably come for the LDL cholesterol goal of <2.6 mmol/L to be abandoned.